Виды рода Philopterus (Mallophaga, Ischnocera) от жаворонков фауны СССР - Федоренко, И.А. (Вестник зоологии, 1984)
Species of the Genus Philopterus (Mallophaga, Ischnocera) from the Larks of the USSR Fauna. Fedorenko I. A.— Vestn. zool., 1984, No. 3. Four species parasitizing the larks (genera Lullula, Eremophila and Melanocorypha) are described as new. Ph. arboreus sp. n. from the wood lark is similar to Ph. stadleri, Ph. stepposus sp. n. from the calandra lark, and Ph. turkmenicus sp. n. from Eastern calandra lark are allied to Ph. alexanderkoenigi, Ph. kekilovae sp. n. from the horned lark differs from all known representatives of the genus. Diagnostic characters: head shape, clypeal plates complex structure and genitalic armatures in male and female. A key to Philopterus species except